The comprehensive assessment and critical analysis of mycotoxins present in desiccated food specimens that were meticulously gathered from the Libyan market. (Comprehensive Journal of Science, 2025)
Background: Detecting and preventing mycotoxin contamination in dry food is crucial for ensuring food safety and protecting public health. Mycotoxins, toxic compounds produced by fungi, can contaminate a wide range of food products, including cereals, nuts, and dried fruits, posing significant health risks. Effective detection and prevention strategies are essential to mitigate these risks. This response explores the current methods for detecting mycotoxins and strategies for preventing their contamination in dry food.Objectives: the present study aimed to evaluate 3 mycotoxins in cereals and some selective dry foodMethods: The Eliza R. biopharm methodology employs ELISA for  mycotoxin detection in food matrices was applied  Results: a total of 178 samples were examined for the presence of mycotoxin residues. The results showed that,   51 samples were assessed for Ochratoxin residues, which varied from 0.250 to 79.71 µg/kg. Conversely, the maximum concentration of Ochratoxin residue was observed in grounded coffee, whereas dry coffee and wheat flour exhibited the    lowest levels, accompanied by low standard deviation values across all samples. Moreover, a total of 93 samples were assessed for Oflatoxin residues, which varied from 0.300 to 4.85 µg/kg. Conversely, the maximum concentration of Ochratoxin residue was observed in Millet, whereas dry Corn crisps ,Green tee  , Almond and Red tee exhibited the    lowest levels, accompanied by low standard deviation values across all samples. On the other hand, a total of 34 samples were assessed for DON residues, which varied from 18.5 to 104.30 µg/kg. Conversely, the maximum concentration of DON residue was observed in corn while, Wheat flower, soya bean, and barley Wheat exhibited the lowest levels, accompanied by low standard deviation values across all samples.
Keywords: ochratoxin – DON – aflatoxin – cereals.